MODEL PENGAWASAN DAN TATA HUBUNGAN KEWENANGAN DALAM UPAYA PENCEGAHAN TINDAK PIDANA KORUPSI DANA DESA - Sherlock Halmes Lekipiouw; Hendrik Salmon; Natanel Lainsamputty (Universitas Muhammadiyah Ponorogo, 2021)
This research was conducted to review and analyze the technical aspects of the law, especially in the approach of constitutional law and administrative law related to governance and accountability and responsibility in managing village funds and how efforts are made in the framework of prevention, especially the supervision aspect of minimizing the existence of village funds. Misuse and corruption in the use of village funds by village officials. This study uses a socio-legal method (doctrinal analysis of the law) using 3 (three) approaches, namely first, the conditional approach, which refers to the village fund management policy strategy, mainly related to the high cases of corruption in village funds; (2) statute approach, which refers to the system to legislation relating to the management of village funds; and (3) legal policy, which relates to government policies in terms of monitoring and preventing corruption in the direction of village funds. All stages in this research are carried out using a community service research scheme that has been determined by the research institution to be carried out by the Research Team in the field of constitutional law studies and administrative law. The focus of the research will be directed at structuring the relationship of authority between law enforcement agencies and the government, in this case, the Government Internal Supervisory Apparatus (APIP), in conducting supervision and law enforcement on the management of village funds. This is intended to obtain a model and policy framework for managing village funds free from criminal acts of corruption to realize the principles of transparency and accountability by the applicable laws and regulations.